A higher colour grade yellow plaque was detected at one year after implantation of an everolimus-eluting stent than after a zotarolimus-eluting stent. Issue 1 (7th September 2013) - Matsuo, Koshi; Ueda, Yasunori; Nishio, Mayu; Hirata, Akio; Asai, Mitsutoshi; Nemoto, Takayoshi; Murakami, Ayaka; Kashiwase, Kazunori; Kodama, Kazuhisa
Abstract : Objective: Neoatherosclerosis or atherosclerosis progression is one of the mechanisms of long-term stent failure. Yellow plaque detected by angioscopy has been associated with advanced atherosclerosis and the future risk of a coronary event. We compared the yellow colour of the stented segment between zotarolimus-eluting stents (ZES) and everolimus-eluting stents (EES) at 1 year after implantation. Design: Cross-sectional study. Patients: Consecutive patients underwent angioscopic examination 1 year after the implantation of ZES (n=45) or EES (n=45) at a de novo native coronary lesion. Main outcome measures: The maximum yellow colour grade (grade 0–3) of the stented segment, maximum and minimum neointima coverage grade (grade 0–2) and the presence of thrombus were examined. The neointima heterogeneity index was calculated as maximum − minimum coverage grade. Results: Maximum yellow colour grade was higher in EES than in ZES (1.3±0.9 vs 0.4±0.8, p<0.001) and maximum (2.0±0.2 vs 1.2±0.5, p<0.001) and minimum (1.5±0.6 vs 0.7±0.5, p<0.001) coverage grade was higher in ZES than in EES. The neointima heterogeneity index was not different between ZES and EES (0.4±0.5 vs 0.5±0.6, p=0.42). The incidence of thrombus was very low and was not different between ZES and EES (2% vs 4%, p=0.55). Conclusions: Although both ZES and EES had good healing with homogeneous neointima coverage and a low incidence of thrombus, EES had more advanced atherosclerosis as shown by the presence of higher grade yellow plaque than ZES at 1 year after implantation.